Development of a Comprehensive Quality-of-Life Measure for Facial and Torso Acne. Issue 3 (May 2018) - McLellan, Chelsea; Frey, Marc P.; Thiboutot, Diane; Layton, Alison; Chren, Mary-Margaret; Tan, Jerry
Background: Acne is a chronic skin disorder which generally presents in adolescence but continues into adulthood, and negatively affects both physical and psychosocial well-being. Presently, there are no validated acne-specific quality-of-life (QoL) measures that include dimensions for both facial and torso acne. Objective: The objective of this study was to develop a QoL instrument for both facial and torso acne (CompAQ) in accordance with recommended standards. Methods: A literature review and Delphi survey of patients and clinicians were used to develop the conceptual framework for outcomes perceived important to acne patients. An initial version of the measure was developed, CompAQ-v1, and pilot tested with patients via cognitive interviews. Results: The Delphi survey generated 4 domains (physical, psychological, sociological, and treatment) and 54 items. These, along with a literature review and input from clinical experts, informed the development of the CompAQ-v1. Eleven cognitive interviews were conducted, resulting in the second version of the measure, CompAQ-v2. Psychometric validation resulted in the final 20-item CompAQ measure comprising 5 domains. An abbreviated 5-item measure was also developed (CompAQ-SF). Conclusion: CompAQ and CompAQ-SF are instruments intended to evaluate QoL in patients with acne on their face or torso. The former is a 21-item QoL intended for research, while the latter is intended for clinical practice.